Requirements of feeding dairy cows for optimum milk production - Sharma, Manoj (Indian Farming, 2016)
It is suggested that the rations should be balanced not only for the milking herd, but also for each category of the animals, i.e. heifer and dry cows. Rations that are deficient in any particular nutrient can decrease milk production, reproductive efficiency, growth rate and cause health problems. On the other hand, rations that contain excess nutrients decrease profit and may result in health problems.